A performer's guide to the piano music of Samuel Adler - Gowen, Bradford, 1946- (University of Rochester Press, 2022)
"American composer Samuel Adler has composed a huge and multi-faceted body of works ranging from symphonies, concertos, and oratorios to solos for every standard Western instrument, to a rich trove of vocal and choral music, to pieces for students. Among them, encompassing his compositional life of some seventy years, is an array of works for the piano: three concertos; fifteen solo pieces and sets of pieces; a sonata for two pianos; and four volumes of music for beginning and intermediate players. Bradford Gowen writes about each of these works with the knowledge of one who has studied, performed, and recorded Adler's piano music and has previously written about it. He begins with an overview of stylistic and pianistic traits found throughout these pieces and then examines each work chronologically according to genre, in a two-part format. The first part is an essay on the work's style, emotional content, and unique features, which at the same time places the work in the context of other music by Adler and by additional composers from the present and past eras. The second part, informal and practical, is directed to a pianist interested in getting to know this music. As a "lesson" on the piece, it offers specific suggestions for practicing and interpretation and many solutions to technical challenges. Rounding out the book are an in-depth interview with the composer plus six invaluable appendices"--